De la crainte de la damnation éternelle aux prémisses de l’angoisse existentielle contemporaine : inquiétudes sotériologiques et eschatologiques chez William Hale White (« Mark Rutherford ») - Jean-Michel Yvard (Cahiers Victoriens et Edouardiens)
In the Victorian period, the anxiety induced by old age and by the fear of death seems to have been particularly widespread. Indeed, in the context of a relentless secularisation of world views, man’s uncertainties about his personal fate after death were bound to increase. At the beginning of the period, it is true, a rising fear concerning man’s as well as the world’s salvation was counteracted, at least to a certain extent, by a belief in progress, particularly in the field of science. Although man’s survival as an individual was more and more often put into question, it remained possible to believe in an endless improvement of human societies and the world in general. Gradually, however, the fear of a final degeneration of our world began to be induced by scientific knowledge itself, particularly by discoveries in the field of thermodynamics, which predicted the extinction of the sun as well as the thermal death of the universe.To what extent did traditional uncertainties concerning man’s salvation increase in this context? How did these fears often secularise themselves, opening the way to our contemporary « existential anguish » ? Such are some of the questions which are raised in this paper through a study of the autobiographical and fictional writings of William Hale White (« Mark Rutherford »).